Neurotoxins - Eric McDuffie, J. (IntechOpen, 2018)
Toxicologists seek to better understand the myriad of mechanisms responsible for neurotoxins. Because the incidence of neurobehavioral hazards and risks of exogenous compounds (e.g., natural toxins, synthetic molecules, and therapeutic agents) remain a subject matter of interest, predictive tools have evolved, including but not limited to novel translational in vitro models, biomarkers, newer epidemiological research tools, and well-accepted best practices for diagnosing neurotoxins in clinical practice. Taken together, the foreseen need to highlight some of the more appreciated and/or emerging tactical approaches in neurotoxicology results in a "one-stop reference" book, Neurotoxins.